Acute and sub-acute toxicity of ethanol extracts of Hagenia abyssinica and Rumex abyssinicus flowers in Swiss albino mice - Hirut Basha Gemeda; Asfaw Debella; Milkyas Endale; Abiy Abebe; Meharu Mathewos; Wossene Habtu; Dinkenesh Chalchisa; Betelhem Getachew; Menal Hassen; Hassen Mamo (PLoS ONE, 2025)
Background Hagenia abyssinica (Bruce) J.F. Gmel (Family: Rosaceae) and Rumex abyssinicus Jacq (Family: Polygonaceae) are valuable medicinal plants traditionally used in Ethiopia to treat various diseases. Recent studies have also demonstrated that solvent extracts of these plants exhibit molluscicidal activities under laboratory conditions, highlighting their potential for snail control. However, limited information is available regarding their safety profiles. Objective This study aimed to evaluate acute, and sub-acute toxicity of 70% ethanol extracts of H. abyssinica and R. abyssinicus flowers in Swiss albino mice, following the Organization for Economic Co-operation and Development guidelines 423 and 407. Methods In the acute toxicity study, both extracts were administered orally to experimental groups at varying concentrations (mg/kg bodyweight): 5, 50, 300, and 2000. For the sub-acute toxicity study, both extracts were given to the experimental groups at doses (mg/kg) of 125, 250, and 500 daily for 28 days. Blood samples were collected from each mouse and analyzed for hematological and biochemical parameters. Additionally, the heart, liver, and kidneys were excised, stained, and examined for potential histopathological effects. Results The acute toxicity study revealed no noticeable changes in behavior at the highest oral dosage of 2000 mg/kg. In the sub-acute toxicity study, no statistically significant changes were observed in hematological and biochemical parameters compared to the control group. Similarly, no abnormal histological findings were noted in the examined organs in comparison to the control group. Conclusion These findings indicate that flower extracts of both plants did not show significant toxicity to laboratory mammals at an oral dosage of 2000 mg/kg.